Interventions to improve adherence/compliance to home noninvasive positive pressure ventilation in stable hypercapnic chronic obstructive pulmonary disease patients: A systematic review protocol - Amani Kacem; Imen Ben Saida; Dhekra Chebil; Helmi Ben Saad; Mohamed Boussarsar (PLoS ONE, 2025)
Introduction Chronic obstructive pulmonary disease (COPD) is a prevalent condition often leading to chronic hypercapnic respiratory failure in its advanced stages. Home noninvasive positive pressure ventilation (Home-NIPPV) has emerged as a key therapeutic strategy for managing stable hypercapnic COPD patients, improving survival rates, and enhancing quality of life. Despite these benefits, patient adherence/compliance to Home-NIPPV remains a significant challenge, hindered by various barriers. The present paper is a protocol of a systematic review that aims to identify and evaluate interventions designed to improve adherence/compliance to Home-NIPPV in stable hypercapnic COPD patients. Methods The protocol is developed following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses Protocols guidelines and was registered in PROSPERO (CRD42024581616). A comprehensive literature search across PubMed, Scopus and Cochrane Library will be conducted. Eligible studies will include randomized controlled trials that focus on interventions that aims to improve adherence/compliance to Home-NIPPV in stable hypercapnic COPD patients. Data extraction will be meticulously carried out by two independent reviewers. The Joanna Briggs Institute critical appraisal tool will be utilized to assess the quality and risk of bias of the included studies. The findings of this systematic review will be synthesized to provide a thorough understanding of effective strategies to enhance adherence/compliance to Home-NIPPV in stable hypercapnic COPD patients. Conclusion The results of this review could inform clinical practice and guide the development of targeted strategies to improve adherence/compliance to Home-NIPPV and consequently outcomes in stable hypercapnic COPD patients. Registration This protocol was registered in the International Prospective Register of Systematic Reviews under the reference code CRD42024581616.